A Well-Trained Team During Anaphylactic Shock After Rocuronium in a Patient With Aortic Stenosis: A Case Report - Macharadze, Tamar; Davies, Andrew; Fedor, Igor (Frontiers in Medicine, 2020)
A 66-year-old patient with aortic stenosis was scheduled for an aortic valve replacement and coronary artery bypass surgery. Anesthesia was induced by intravenous injection of midazolam, fentanyl, and propofol. After administration of rocuronium, he developed anaphylactic shock, which was diagnosed by clinical signs, vital parameters, and unresponsiveness to the usual vasopressors. After 30 min of cardiopulmonary resuscitation, the patient survived without any neurological deficits. This case is a reminder that early recognition and treatment of intraoperative hypersensitivity reactions are imperative. Anesthetists should also receive simulation training to achieve an adequate experience in a safe environment. With a well-trained team, it is possible to save the life of patients with aortic stenosis.